Analisis Faktor-Faktor Yang Mempengaruhi Pengeluaran Pangan di Kelurahan Andalas Kecamatan Padang Timur - Esa Diya Wahyuni; Gusriati; Andri (Jurnal Research Ilmu Pertanian, 2023)
This study aims to determine the share of household food expenditure in Andalas Village, Padang Timur District, Padang City and analyze the influence of household income, housewife's formal education level, number of family members, and age of marriage on household food expenditure. This research was conducted in August 2021, with a total sample of 82 people. The research technique used is a survey technique. The data analysis used is descriptive quantitative using SPSS Version 18 program. The results of the study are as follows: the share of household food expenditure in Andalas Village, Padang Timur District, Padang City is 26.21%. Factors of household income, level of formal education of housewives, number of family members, and age of marriage together (simultaneously) have a significant effect on food expenditure, partially which has a significant effect on household food expenditure is household income, number of family members. The coefficient of determinant (R2) is 0.73, and the correlation coefficient (R) is 0.854